WSES/GAIS/SIS-E/WSIS/AAST global clinical pathways for patients with intra-abdominal infections - Sartelli, Massimo; Coccolini, Federico; Kluger, Yoram; Agastra, Ervis; Abu-Zidan, Fikri M; Abbas, Ashraf El Sayed; Ansaloni, Luca; Adesunkanmi, Abdulrashid Kayode; Atanasov, Boyko; Augustin, Goran; Bala, Miklosh; Baraket, Oussama; et al. (World journal of emergency surgery, 2021)
Intra-abdominal infections (IAIs) are common surgical emergencies and have been reported as major contributors to non-trauma deaths in hospitals worldwide. The cornerstones of effective treatment of IAIs include early recognition, adequate source control, appropriate antimicrobial therapy, and prompt physiologic stabilization using a critical care environment, combined with an optimal surgical approach. Together, the World Society of Emergency Surgery (WSES), the Global Alliance for Infections in Surgery (GAIS), the Surgical Infection Society-Europe (SIS-E), the World Surgical Infection Society (WSIS), and the American Association for the Surgery of Trauma (AAST) have jointly completed an international multi-society document in order to facilitate clinical management of patients with IAIs worldwide building evidence-based clinical pathways for the most common IAIs. An extensive non-systematic review was conducted using the PubMed and MEDLINE databases, limited to the English language. The resulting information was shared by an international task force from 46 countries with different clinical backgrounds. The aim of the document is to promote global standards of care in IAIs providing guidance to clinicians by describing reasonable approaches to the management of IAIs.
Keywords: Anti-Infective Agents; výsledek terapie; Intraabdominal Infections; Sepsis; antibakteriální látky; Peritonitis; Treatment Outcome; kritické cesty; Intra-abdominal infections; lidé; antiinfekční látky; Anti-Bacterial Agents; nitrobřišní infekce; Humans; Critical Pathways